2017
DOI: 10.12783/dtetr/icia2017/15646
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of Aerodynamic Characteristics of High Temperature Superconducting Maglev-Evacuated Tube Transport System

Abstract: In the high temperature superconducting maglev-evacuated tube transport (HTS Maglev-ETT) system, the air drag is the most principal resistance to the speed improvement and energy conservation. Considering the aerodynamic performance of the HTS Maglev-ETT system has great significance in practical application. As the first step, we experimentally explored the influence of velocity, blockage ratio and airshaft on the air drag of a running maglev vehicle at atmospheric pressure (95.6 kPa in Chengdu), coupled with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…Liu et al [17] modeled the aerodynamic calculation model of high-speed train with the evacuated tube under low-pressure environment, studied the influence of air pressure, blockage ratio and train's running speed on the aerodynamic drag of the train, and gave the optimal relationship between air pressure, blockage ratio and train's speed of the evacuated tube transportation system. Bao et al [18] found the shape of the train body and the structure of the tube can affect the aerodynamic drag, and the blockage ratio is the main factor. In addition, Kim et al [19] also found that when shock waves are generated during the tube train operation, the aerodynamic drag will increase dramatically.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [17] modeled the aerodynamic calculation model of high-speed train with the evacuated tube under low-pressure environment, studied the influence of air pressure, blockage ratio and train's running speed on the aerodynamic drag of the train, and gave the optimal relationship between air pressure, blockage ratio and train's speed of the evacuated tube transportation system. Bao et al [18] found the shape of the train body and the structure of the tube can affect the aerodynamic drag, and the blockage ratio is the main factor. In addition, Kim et al [19] also found that when shock waves are generated during the tube train operation, the aerodynamic drag will increase dramatically.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [17] modeled the aerodynamic calculation model of high-speed train with the evacuated tube under low-pressure environment, studied the in uence of air pressure, the blockage ratio and train's running speed on the aerodynamic drag of the train, and gave the optimal relationship between air pressure, blockage ratio and train's speed of the evacuated tube transportation system. Bao et al [18] found the shape of the train body and the structure of the tube can affect the aerodynamic drag, and the blockage ratio is the main factor. In addition, Kim et al [19] also found that when shock waves are generated during the tube train operation, the aerodynamic drag will increase dramatically.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in the study of aerodynamic heating of the tube train, most scholars adopt a two-dimensional geometric model, which makes it impossible to further observe the temperature distribution on the train surface and in the tube. In the future, most of the trains in the tube will be maglev trains [1] , some types of the maglev trains' external equipment cannot be in high temperature environment, such as the high temperature superconducting maglev of Southwest Jiaotong University [18] , whose bottom contains several cryostats similar to the wheels of wheel-rail trains, which need to be far away from high temperature environment. Therefore, it is necessary to study the in uence of the initial ambient temperature on the aerodynamic heating and the temperature distribution in the tube.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [17] modeled the aerodynamic calculation model of high-speed train with the evacuated tube under low-pressure environment, studied the in uence of air pressure, blockage ratio and train's running speed on the aerodynamic drag of the train, and gave the optimal relationship between air pressure, blockage ratio and train's speed of the evacuated tube transportation system. Bao et al [18] found the shape of the train body and the structure of the tube can affect the aerodynamic drag, and the blockage ratio is the main factor. In addition, Kim et al [19] also found that when shock waves are generated during the tube train operation, the aerodynamic drag will increase dramatically.…”
Section: Introductionmentioning
confidence: 99%